Role of government initiatives in addressing challenges faced by SMEs in working towards service excellence : a grounded theory study. - Pang, Yang Yang. (2013)
In recent years, service has become a differentiating factor among companies to attract and retain their customers. Large companies have been active in building a skilled workforce and having an effective management system, which enables them to achieve service excellence. On the other hand, small companies are far from achieving service excellence due to limited resources and manpower. The government seeks to help these small companies by introducing various initiatives targeted at their needs. However, instead of seeing positive results, these companies continue to lag behind in displaying service excellence.